1993
DOI: 10.1002/food.19930370106
|View full text |Cite
|
Sign up to set email alerts
|

Effect of sex hormones on copper, zinc, iron nutritional status and hepatic lipid peroxidation in rats

Abstract: Sex dependence of copper, zinc, iron nutritional status and hepatic lipid peroxidation was studied in gonadectomized, hormone substituted and sham-operated male and female rats. The experiment was performed on H-Wistar rats (106 +/- 10 g) fed conventional laboratory food ad libitum for 12 weeks. The estrogen dependence of copper status is fully confirmed by the results of this study. In hormonally active females the malondialdehyde production was depressed which is supposed to be connected with high copper and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

1995
1995
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 18 publications
1
4
0
Order By: Relevance
“…In our study, the administration of testosterone to rabbits resulted in elevated MDA level in plasma ( P < 0.05). This results in agreement with that of Wachnik et al. (1993), who reported that testosterone accelerated the hepatic LPO in rats.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In our study, the administration of testosterone to rabbits resulted in elevated MDA level in plasma ( P < 0.05). This results in agreement with that of Wachnik et al. (1993), who reported that testosterone accelerated the hepatic LPO in rats.…”
Section: Discussionsupporting
confidence: 93%
“…However, the exact role of testosterone and their relationship with oxidative processes such as lipid peroxidation (LPO) in the progression of atherosclerosis remains unclear. Wachnik et al. (1993) have shown that testosterone had a marked prooxidant effect, activating LPO in the liver of male rats.…”
Section: Introductionmentioning
confidence: 98%
“…We found gender differences in MMT in almost all macular areas in younger but not in older subjects, which suggest that the sexual dimorphism of the human retina may depend on gonadal hormone levels. Indeed, estrogen receptors seem to protect the retina against age-inflicted injury [ 23 , 24 ], partly by inhibiting lipid peroxidation [ 15 , 63 , 64 ]. Exposure to endogenous oestrogens has been associated with lower risk for EAMD [ 18 , 19 ], and exogenous estrogens seem to protect against late age-related degeneration [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…Increased levels of testosterone have been reported to be associated with lower levels of ferritin [34]. Moreover, estrogens increase levels of Cu through Cp [35] and also have effects on Fe status. Estrogens directly contribute to Fe homeostasis by regulating hepatic hepcidin expression through estrogens response elements (ERE) in the promoter region of the hepcidin gene.…”
Section: S T a C C E P T E Dmentioning
confidence: 99%